Human-elephant conflict in Pu Mat National Park region, Nghe An Province: current status and impact on the conservation atitude of local residents - Dang, Nguyen Xuan; Nghia, Nguyen Xuan; Dat, Nguyen Tien; Luong, Nguyen Thanh (Academia Journal of Biology, 2020)
Pu Mat National Park (NP) region is designated by the Government of Vietnam as a priory area for conservation of the Asian elephant. Out of three elephant groups currently inhabited Pu Mat NP region, only the group in Anh Son District (Anh Son elephant group) causes severe human-elephant conflict (HEC) with significant economic damage for local villagers and rubber farms, human casualties, and induced psychological pressure for local residents. Because of the HEC, support for the elephant conservation of local residents was significantly reduced and the retaliatory killing of an elephant happened in 2011.This study assessed the HEC status in Anh Son District and identified the main causes of HEC here.